ÅCómo enseñar argumentación jurídica? (2017)
This research responds to an interest in improving through my pedagogical practice the argumentative competences of students of Juridical Argumentation II of the Law School of the Sergio Arboleda University. The research is framed under the methodology called action research, which was developed during the second half of 2014. Under the categories: learning, communicative and transversal competences, curriculum, pedagogical practices from the role of the teacher, the student's role, the use of problems and role play, and the analysis of ethical reflections made in class, in addition to evaluation. The instruments used were mainly: interviews with teachers, field diary, class recordings, survey and focus group with students. The question that is intended to answer is: how do my pedagogical practices, enriched through the reflection of the instruments used in the action research, contribute to the development of the argumentative competences of my students? The evidenced findings are presented as a result of the spiral analysis process, typical of the methodology used through the categories listed. The construction of secure participation environments, in which students are the protagonists of the learning processes and the spokespersons of the same, energize the argumentative competences. The subject is pertinent given the changes that have had the legal practice, in which the orality is taking up a preponderant role.--Tomado del Formato de Documento de Grado.